PERANAN AUDIT INTERNAL DAN PENCEGAHAN FRAUD DALAM MENUNJANG EFEKTIVITAS PENGENDALIAN INTERNAL (Studi Kasus Pada Yayasan Internusa Surakarta) - Istiyawati Rahayu, Ety Meikhati (Paradigma, 2015)
College management autonomy which is regulated in IndonesianGovernment Regulation number 4 in 2014 on non-academic fields, internal audit is used to control and development of quality higher education. The position of internal audit as a supporting activity such as finance, assets, organization and human resources. This study aimed to examine the effect of the role of internal auditand fraud prevention on the effectiveness of internal control at the Internusa Foundation. The method used in this research is descriptive analysis method and multiple linear regression analysis. The sample used in this study consisted of 37 respondents consisting of 4 managers of foundations, 3 foundation staff, 30 lecturers/staff APIKES and AKBID Citra Medika. Of the 37 questionnaires distributed all the back and can be analyzed.Â  The results showed that (1) the role of internal audit affect the effectiveness of internal controls, (2) the prevention of fraud significantly influence the effectiveness of internal controls, and (3) the role of internal audit and fraud prevention simultaneously significant effect on the effectiveness of internal control. The role played by internal audit and fraud prevention simultaneous influence on the effectiveness of internal controls by 71.2% and the remaining 28.8% is influenced by other factors not examined. This study supports previous research which revealed the importance of internal audit in institutions of higher education.